Probing the potential of bioactive compounds of millets as an inhibitor for lifestyle diseases: molecular docking and simulation-based approach - Nagre, Kajal; Singh, Nirupma; Ghoshal, Chandrika; Tandon, Gitanjali; Iquebal, Mir Asif; Nain, Tarsem; Bana, Ram Swaroop; Meena, Anita (Frontiers in Nutrition, 2023)
Millets are becoming more popular as a healthy substitute for people with lifestyle disorders. They offer dietary fiber, polyphenols, fatty acids, minerals, vitamins, protein, and antioxidants. The nutritional importance of millets leads to the present in-silico study of selective bioactive compounds docked against the targets of lifestyle diseases, viz., diabetes, hypertension, and atherosclerosis using molecular docking and molecular simulations approach. Pharmacokinetic analysis was also carried out to analyse ADME properties and toxicity analysis, drug-likeliness, and finally target prediction for new targets for uncharacterized compounds or secondary targets for recognized molecules by Swiss Target Prediction was also done. The docking results revealed that the bioactive compound flavan-4-ol, among all the 50 compounds studied, best docked to all the four targets of lifestyle diseases, viz., Human dipeptidyl peptidase IV (−5.94 kcal mol−1 binding energy), Sodium-glucose cotransporter-2 (−6.49 kcal mol−1) diabetes-related enzyme, the Human angiotensin-converting enzyme (−6.31 kcal mol−1) which plays a significant role in hypertension, and Proprotein convertase subtilisin kexin type 9 (−4.67 kcal mol−1) for atherosclerosis. Molecular dynamics simulation analysis substantiates that the flavan-4-ol forms a better stability complex with all the targets. ADMET profiles further strengthened the candidature of the flavan-4-ol bioactive compound to be considered for trial as an inhibitor of targets DPPIV, SGLT2, PCSK9, and hACE. We suggest that more research be conducted, taking Flavon-4-ol into account where it can be used as standard treatment for lifestyle diseases.